Extraocular sebaceous carcinoma of the vulva. A case report - Reyna-Villasmil, Eduardo (2019)
Sebaceous carcinoma is a rare malignant tumor of the skin that usually appears in the head and neck region. Its clinical course is aggressive and local recurrences - distant metastases are common. Some cases of sebaceous carcinoma of the female genital tract have been reported. Although sebaceous glands are prominent in the vulva, sebaceous carcinomas rarely occur in this location. Little is known about the behavior and prognosis of this type of cancer. We present a case of a 69-year-old patient with a history of a 3 x 2-centimeter tumor for 9 months in the left labium majus. She had no medical or family history of malignant neoplasms. Increases in size was observed during this period, but otherwise, she was asymptomatic. Lesion was completely excised. The tumor was composed of lobes of tumor cells with sebaceous differentiation. Histopathological report revealed vulvar sebaceous carcinoma. It must be differentiated from other vulvar carcinomas that are morphologically similar but biologically different.